Perencanaan Msdm Secara Global dan Perbedaan Praktik di Berbagai Negara, Aktivitas Bisnis Internasional Mempengaruhi MSDM - Iskandar Muda Nasution; Suhendri Suhendri; Marzuti Isra; Purjianto Purjianto; Diki Surya Darma; Muhammad Darmawansyah; Muhammad Teguh Juliansyah; Nicolas Sinaga; Frenly Ricardo Simamora (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2026)
This study examines global Human Resource Management (HRM) planning, the differences in HRM practices across countries, and the impact of international business activities on HRM management strategies. The method used is a literature review with a qualitative descriptive approach through an analysis of literature related to Strategic Human Resource Management (SHRM). The results show that SHRM plays a vital role in aligning HRM strategies with organizational business strategies amidst global challenges. Human resource development, job analysis, and workforce forecasting are found to be key factors in improving organizational effectiveness. Furthermore, the application of the principle of equal employment opportunity contributes to the creation of a fair and professional work environment. Overall, strategic and integrated HRM planning is a crucial element in increasing organizational competitiveness in the era of globalization, where flexibility and responsiveness to market and technological changes are key to success in HRM management at the international level.